2019
DOI: 10.35336/va-2019-2-19-28
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Noninvasive Epi- Endocardial Electrocardiographic Imaging Accuracy Using Right Ventricular Endocardial Pacing

Abstract: Invasive electroanatomical mapping of polymorphic and unstable ventricular arrhythmias is a complex and laborious task. Noninvasive epi-endocardial ElectroCardioGraphic Imaging (ECGI) is a novel beat-to-beat mapping technique. The present work is a second part of single-center single-blind cross-sectional study to verify epi-endocardial ECGI accuracy. This part is particularly dedicated to investigate ECGI accuracy during right ventricular endocardial pacing followed by polygon model quality assessment and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Further analysis included evaluation of typical morphology of paced QRS complex. All other stages of registration of multichannel surface ECG, CT and processing of non-invasive imaging data were identical to those previously published in our recent work [3,4]. Export of three-dimensional polygo-nal models in the VTK format and original multichannel ECG recordings in the specific text format was performed using software "Amycard 01C".…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis included evaluation of typical morphology of paced QRS complex. All other stages of registration of multichannel surface ECG, CT and processing of non-invasive imaging data were identical to those previously published in our recent work [3,4]. Export of three-dimensional polygo-nal models in the VTK format and original multichannel ECG recordings in the specific text format was performed using software "Amycard 01C".…”
Section: Methodsmentioning
confidence: 99%
“…According to the new FRA-V algorithm, the area of early activation was determined automatically on the three-dimensional polygonal model of the ventricles as the point with the highest value of the correlation coefficient of the similarity maps (Figures 1, 2). In the same way to previous studies, the exact position of the pacing electrode in the IVS was evaluated during CT. Then the geodesic distance was measured (along the surface) between the tip of the RV electrode and the center of the early activation zone that were marked with a tag [3,4]. All study measurements were performed only on the endocardium of the epi-endocardial three-dimensional polygonal model (endo epi-endo model) in each patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of recent validation studies showed high precision of non-invasive electrocardiographic imaging (ECGI) for focal arrhythmia localization [1][2][3][4][5]. Successful ablation of arrhythmias and colocalization of the early activation zone (EAZ) with the pacing lead tip can be reliable methods of accuracy verification.…”
Section: Introductionmentioning
confidence: 99%
“…Эта методика основана на решении обратной задачи электрокардиографии в форме потенциалов и позволяет с высокой точностью реконструировать эпи-и эндокардиальные электрограммы (ЭГ) и визуализировать электрофизиологические процессы на основе различных активационных карт [6]. Использование НЭФК было продемонстрировано в ряде исследований и показало достаточно высокую точность в топической диагностике желудочковых аритмий [7][8][9] и РЧА также еще раз продемонстрировало высокую точность новой методики, показанную в предыдущих исследованиях [7][8][9]. Примечательно, что другие похожие системы НЭФК [14] позволяют реконструировать ЭГ и активационные карты только на эпикардиальной поверхности сердца, тогда как электрофизиологическая информация на эндокарде в ряде случаев имеет ключевое значение для диагностики аритмий.…”
unclassified